Ecologia alimentar de carnívoros em remanescentes de mata atlântica entremeados por matriz silvicultural, na região sul do Brasil - Juraszek, Adriana (2014)
The objective of this study was to investigate the composition of sympatric carnivores diet living in forest fragments of Atlantic forest interspersed with Pinus sp. e Eucalyptus sp.The study was conducted in the county of Vargem Bonita and Ponte Serrada, state of Santa Catarina. The information regarding diet were obtained through analysis of feces collected during the period July 2006 to July 2008. The first chapter discusses the composition of the diet of the coati Nasua Nasua, in a subsequent period of fruiting Merostachys skvortzovii, that due to massive seed production causes a higher population of small rodents phenomenon popularly known as ratada, the hypothesis that this event may have influenced the composition of the diet. As there were no data on the composition of the diet for the study area in the period before fruiting M. skvortzovii, the hypothesis was tested based on other studies on the feeding ecology of the species in an Atlantic forest. The results indicate that mammals are the most important (62.1% ii PO) and more frequent items (FO = 100%). The Cricetidae family stood out based on frequency of occurrence (FO = 95.1%) and percentage of occurrence (PO = 59.0%) and Lutreolina crassicaudata based on biomass consumed (PB = 52.2%). In 39.0% of samples were found plant material, but is category was composed exclusively of foliar blades of grass. The observed results show that the fruiting of M. skvortzovii, may have influenced the diet given that the consumption of mammals differs from that recorded for the species in previous studies in the area Atlantic forest. The second chapter of this study evaluated qualitatively and quantitatively the composition of the diet, the width and dietary overlap of five species of felines and they: Leopardus tigrinus, L. wiedii, L. pardalis, Herpailurus yagouaroundi and Puma concolor. For this 460 fecal samples were analyzed and it was found that mammals are the most important items in the diet of cats with emphasis on family Cricetidade which occurred in 386 samples was expected especially for species with smaller. Overall, the results indicate high overlap values for the pairs L. tigrinus -L. pardalis and L. tigrinus -H. yagouaroundi. Despite high overlap valuesobserved during the sampling period we cannot say that competition for resources, species may occupy similar niches, but not identical to exploit food resources in different proportions over time. Furthermore, the abundance of rodents in this period may have allowed high dietary overlap, fact that can be investigated by analysis of the recent carnivorous diet of these, once not there previous study to the region investigated.